The effect of alcohol consumption on the risk of ARDS: a systematic review and meta-analysis - Simou, Evangelia; Leonardi-Bee, Jo; Britton, John (Elsevier, 2017)
BACKGROUND: To conduct a systematic review and meta-analysis evaluating the association between alcohol consumption and the risk of ARDS in adults. METHODS: Medline, EMBASE and Web of Science were searched to identify observational studies evaluating the association between prior alcohol intake and the occurrence of ARDS among adults, published between 1985 and 2015 and with no language restriction. Reference lists were also screened. Demographic baseline data were extracted independently by two reviewers and random-effects meta-analyses were used to estimate pooled effect sizes with 95% confidence intervals. Subgroup analyses were used to explore heterogeneity. RESULTS: Seventeen observational studies (177,674 people) met the inclusion criteria. Metaanalysis of 13 studies showed that any measure of high relative to low alcohol consumption was associated with a significantly increased risk of ARDS (OR, 1.89; 95% CI, 1.45-2.48; I² = 48%; 13 studies); no evidence of publication bias was seen (P = .150). Sensitivity analyses indicated that this association was attributable primarily to an effect of a history of alcohol abuse (OR, 1.90; 95% CI, 1.40-2.60; 10 studies). Also, subgroup analyses identified that heterogeneity was explained by predisposing condition (trauma, sepsis/septic shock, pneumonia; P = .003). CONCLUSIONS: Chronic high alcohol consumption significantly increases the risk of ARDS. This finding suggests that patients admitted to hospital should be screened for chronic alcohol use.